PERAN PERSERIKATAN BANGSA-BANGSA DALAM RESOLUSI KONFLIK KASHMIR: EVALUASI EFEKTIVITAS UNITED NATIONS MILITARY OBSERVER GROUP IN INDIA AND PAKISTAN (UNMOGIP) - Azzahra, Naila Putri; Marsingga, Prilla (Cahaya Ilmu Bangsa, 2025)
The conflict between India and Pakistan over the Kashmir region has persisted since 1947, making it one of the longest-runnnig disputes in the world. To monitor the ceasefire between the two nations, the United Nations (UN) established the United Nations Military Observer Group in India and Pakistan (UNMOGIP) in 1949. Although UNMOGIP aims to observe violations and provide independent reports, its effectiveness remains a subject of debate. India considers this mission irrelevant since the Simla Agreement of 1972, whereas Pakistan continues to support its presencce. This study evaluates the role of UNMOGIP in mitigating approach through document and literature analysis. The findings indicate that UNMOGIP’s effectiveness has declined due to limited mandates, restricted access in Indian territory, and the lack of authority to enforce decisions. Despite its limitations, UNMOGIP remain a symbol of international presencein the Kashmir conflict. Therefore, reforms or new approaches are needed to enchance the UN’s effectiveness in maintaining stability in the region.